Three-dimensional biomimetic head model as a platform for thermal testing of protective goggles for prevention of eye injuries. (April 2019) - Friedman, Rinat; Haimy, Ayelet; Gefen, Amit; Epstein, Yoram
Abstract: Background: The rate of eye injury is steadily rising during military conflicts of the century, with thermal burns being the most common type of injury to the eyes. The present study focuses on assessing the heat resistance properties of military protective goggles using three-dimensional (3D) finite element head modeling fitted with the tested protective gear. Methods: A computational thermal impact was applied onto a 3D biomimetic human head model fitted with two goggle models - sports (Type 1) and square (Type 2). The resultant temperature of the eye tissues and the thermal injury thresholds were calculated by using the modeling, hence allowing to determine the protective efficacy of the goggles objectively, in a standardized, quantitative and cost-effective manner. Findings: Both types of goggles had a dramatic protective effect on the eyes. The specific goggle geometry had no notable effect on the level of protection to the inner tissues against the thermal insult. At the skin level goggles reduced temperatures by 64% under the impact zone, with only a mild difference (10 °C) between the goggles. Interpretation: Little limitations on the shape and geometry of goggles were observed and any structure of goggles can provide an adequate protection against a thermal insult (per se) to inner cranial tissues, assuming the lenses are wide and thick enough to block direct skin contact of the heat insult. It was shown that our 3D biomimetic human head model provides a practical and cost-effective tool for determining the performance level of goggles with different attributed (i.e., shapes and thermal properties). Highlights: A finite element head model has been developed for testing military goggles. Goggles provide considerable thermal protection for eye and optic nerve tissues. For example, adequate goggles may reduce heat impacts of 150 °C to 49 °C. The geometry of goggles could vary and still significantly reduce heat impact.